Condiciones de salud bucal de los recuperadores informales del sector de Guayaquil y de sus familias. Medellín, Colombia, 2003 - Agudelo-S., Andrés Alonso; Gómez-C., Jaime Arturo (Revista Facultad de Odontología Universidad de Antioquia, 2009)
A study was undertaken to characterize the socioeconomic and health conditions of the informal recyclers of the sector of Guayaquil, Medellín - Colombia, that shows how the life conditions define to a large extent their health situation. There, in a population of 68 recyclers and relatives, a transversal descriptive study was carried out in order to find out about their oral health conditions. By means of an oral clinic history some aspects related to their representations and practices in health habits were recognized, also a complete examination, following the design of the III National Study of Oral Health on 1998, was done. The findings indicate to us how this group is in unfavorable conditions with respect to the general population and gives us standards to establish clear intervention strategies that permit to improve their precarious health conditions by offering welfare.